Novel approaches for geospatial risk analytics in the energy–water–food nexus using an EWF nexus node - Maryam Haji (17092915) (2020)
This study introduces a novel energy, water and food nexus ‘Node’ methodology which includes: (a) decentralization using GIS-based approaches; (b) development of composite geospatial risk indicators using the Analytical Hierarchy Process; and (c) assessment of resource utilization. The methodology is applied to open fields agriculture, conventional greenhouses and hydroponic greenhouses in Qatar using the following nine risk factors: temperature, humidity, solar radiation, soil quality (As and Fe concentration), groundwater depth, groundwater recharge rate, groundwater salinity and groundwater pH. The analysis concludes that the critical factors that increase risk in open field farms are weather factors, such as temperature, solar radiation and humidity, with relative weights of 0.18527, 0.16860 and 0.15785, respectively, whilst groundwater factors have the highest impact on conventional and hydroponic greenhouses. Furthermore, although hydroponic greenhouses are more efficient in terms of water consumption in comparison to open fields, they consume more energy due to cooling and desalination requirements. Other Information Published in: Computers & Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.compchemeng.2020.106936